2020
DOI: 10.1111/fare.12488
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Family Functioning: Psychometric Evaluation of the Family Star Plus

Abstract: Objective To examine the psychometric properties of the Family Star Plus, an assessment of family functioning using a collaborative mode of completion between the caseworker and service user. Background The Family Star Plus is widely used to assess strengths and needs within services supporting families. Method In Phase 1, interrater reliability was assessed. Phase 2 established factor structure, internal consistency, item redundancy, and responsiveness. In Phase 3, the Family Star Plus was used to predict chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…They also focus on pilot findings reported in the study of MacKeith (2014) from a much earlier precursor of the Family Star Plus (the first edition of the Family Star), describing agreement on the journey of change in negative terms, when it fact it was substantially higher than frequently cited thresholds (Chaturvedi and Shweta, 2015). Rather surprisingly, they did not mention the inter-rater reliability findings shared with them in manuscript form prior to the publication of Good and MacKeith (2020). Good and MacKeith (2020) showed very good inter-rater reliability for the Family Star Plus (Krippendorff’s α = 0.83), using a much larger sample than MacKeith (2014) and with a chance-corrected inter-rater reliability coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They also focus on pilot findings reported in the study of MacKeith (2014) from a much earlier precursor of the Family Star Plus (the first edition of the Family Star), describing agreement on the journey of change in negative terms, when it fact it was substantially higher than frequently cited thresholds (Chaturvedi and Shweta, 2015). Rather surprisingly, they did not mention the inter-rater reliability findings shared with them in manuscript form prior to the publication of Good and MacKeith (2020). Good and MacKeith (2020) showed very good inter-rater reliability for the Family Star Plus (Krippendorff’s α = 0.83), using a much larger sample than MacKeith (2014) and with a chance-corrected inter-rater reliability coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Rather surprisingly, they did not mention the inter-rater reliability findings shared with them in manuscript form prior to the publication of Good and MacKeith (2020). Good and MacKeith (2020) showed very good inter-rater reliability for the Family Star Plus (Krippendorff’s α = 0.83), using a much larger sample than MacKeith (2014) and with a chance-corrected inter-rater reliability coefficient. This article also demonstrated that Star readings predicted hard outcomes, offering further evidence that they can be meaningful and accurately completed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations